Consumo de antibacterianos endovenosos en el servicio de pediatría del hospital iv víctor lazarte echegaray- trujillo en el año 2009” - García Vega, Lucía Victoria (2009)
The indiscriminate use of antibacterials generates a significant increase in the cost of health care, either by the use of more expensive alternatives, trying to avoid the threat of bacterial resistance, or simply the waste of not indicated treatments at dosage or duration of treatment and therefore inadequate, ineffective and potential ecological effects. It is for this reason is that in the present research the main objective was to determine the characteristics of intravenous antibacterials consumption in the Department of Pediatrics IV Víctor Lazarte Echegaray-Trujillo in 2009, based on a parameter such as the standard Prescribed Daily Dose (PDD). The present work of investigation is a descriptive, retrospective and cross-sectional study for which analyzed the consumption of antibacterials produced by the Department of Pediatrics and were served by the Hospital Pharmacy of the hospital during the study period, these data was extracted from the Database Management System of Hospital IV "Víctor Lazarte Echegaray” for further analysis. The drug group that generated the highest consumption was 86.03DDP/100 Cephalosporins with day-beds followed by Aminoglycosides with 44,63 DDP/100camas-dia, while the drug was the most consumed 44,63 DDP/100 Amikacin with day-beds. There were no trends of intravenous antibacterial consumption in the study period since data were not statistically significant, and finally, the drug that had higher cost during the study period was Imipenem / Cilastatin to S/.5 920.67